Karl Polanyi, Viviana Zelizer et la relation marchés-société - Steiner, Philippe (Revue du MAUSS, 2007)
After a brief study on the place given to Polanyi’s thought in contemporary economic sociology, the paper examines Zelizer’s works on money and her opposition to Polanyi’s thesis on embeddedness, grounded on the symetry between markets and social life.
Keywords: ZELIZER, Viviana; embeddedness

Who is right about the modern economy: Polanyi, Zelizer, or both? - Steiner, Philippe (Theory and Society, 2009)
Zelizer’s work may be read as an attack on the central Polanyian thesis: that the market system threatens social life by the undue prominence it lends the economy in the organization of modern society. The recent publication of Viviana Zelizer’s The Purchase of Intimacy (2005a) is therefore an excellent opportunity to review the general trend of her work Zelizer 1979, 1985, 1994, and contrast her leading ideas to the central thesis that gives Polanyi’s work its particular flavor: the danger encapsulated in the use of modern money and the functioning of the market system.
Keywords: ZELIZER, Viviana; market system; money

Cartographie des échanges - Steiner, Philippe (Nouvelles Perspectives en Sciences Sociales, 2014)
In this article, I examine the main typologies of transaction that have been built from Auguste Comte to Karl Polanyi, Marcel Mauss, and Philippe Descola. Then, I suggest to reconsidering Polanyi's typology, the most common in contemporary economic sociology, and to limit the time span to modern societies. Accordingly, it is possible to map seven forms of transaction and the related institutions at work in our societies. In conclusion, the political consequences of the existence of these different forms of transaction are highlighted. (English)
Keywords: don; exchange; gift; héritage; inheritance; marché; market; solidarity; solidarité; échange